Computer Graphics Multimedia and Animation
This book will help students build sound concepts which underlie the three distinct but related topics of Computer Graphics, Multimedia and Animation. These topics are of utmost importance because of their enormous applications in the fields of graphical user interfaces, multimedia and animation software development.The treatment of the text is methodical and systematic, and it covers the basic principles for the use, design and implementation of computer graphics systems with a perfect balance in the presentation of theoretical and practical aspects.